Correlations between injury, training intensity, and physical and mental exhaustion among college athletes - Vetter, R. E.; Symonds, M. L. (The Journal of Strength and Conditioning Research, 2010)
The primary purpose of this research was to obtain information concerning injury incidence and perceptions of training intensities and fatigue levels among college athletes via a survey study. A second purpose was to illuminate correlations between the collected data. This study employed an investigator-designed survey instrument administered to 411 NCAA Division II male and female athletes, with 149 completed responses. The survey included 3 themes: injury incidence, training intensity, and physical and mental exhaustion. Men and women spent 4.5 days per week training using moderate- and high-intensity levels. Fifty percent of the total number of athletes reported chronic injury. During the competition season, physical exhaustion occurred "frequently" 30.86 and 23.53% of the time with men and women, respectively. In the noncompetition season, physical exhaustion was "frequently" experienced 19.75 and 17.65% of the time among men and women, respectively. Statistically significant correlations (p < 0.05) were found with acute injury for men and chronic injury for women. Also, training intensity levels and physical and mental exhaustion for men and women were statistically significant. The current investigators found the training involved 2-3 hours of moderate to high intensity 4.5 days per week both during competition and noncompetition; women and men spent 2-3 hours of light intensity 1.31 and 1.45 days per week, respectively. Women and men in addition to training, engaged in 3.78 and 4.43 hours of leisure physical activity per week. The investigators recommend tapering, periodization, and rest to help avoid overuse syndrome, overreaching, and overtraining that leads to excessive physical and mental exhaustion and injury.